Produktivitas Ayam Pedaging Pola Kemitraan di Kabupaten Lombok Barat - Dwi K. Purnamasari; Syamsuhaidi Syamsuhaidi; K.G Wiryawan; Erwan Erwan; Sumiati Sumiati; W. Zohriana; Y. Arifin (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
ABSTRACTThis study aims to determine the level of productivity of broilers in the partnership farm system in relation to the quality of feed  provided by partner companies. The research was conducted in 2 (two) stages; Phase I. Survey of  feeding system in partnership system of broiler farming in West Lombok. The parameters observed included: type of feed offered, the amount provided and frequency of feeding, harvest weight, and FCR. Phase II. Evaluation of the chemical composition of the diet used in partnership broiler farming system. The parameters observed included: the moisture, ash, protein, fat and  fiber. The data obtained were tabulated and discussed descriptively. Based on the survey results, there are 8 partnership companies, namely PT. MSJ, PT. BBB, PT. Samsung, PT. DMC, PT. BSS, PT. FMS, PT. KUS  and PT. PAL, and 6 types of feed used, namely S12, GM-PS, GM 1 EJ, Malindo, Wonokoyo, HD BR1 161. Average feed consumption is 3.24 kg / head / period, with weight gain of 2.10 kg / head / period, with the  FCR value of 1.54. Based on the results of the evaluation of the nutritional content, there is a mismatch, especially the  protein content which is lower (0.01%) as shown in the leaflet of the starter feed from Wonokoyo company. The conclusion of this study is that in general, the complete feed quality used is  in accordance with the SNI based feed quality standards and the broiler productivity produced on partner farms meets the company standards. Nutritional; Complete Feed; Consumption; Weight Gain; Feed Conversion